THE MEASUREMENTS OF SOLENOID INDUCTANCE AND THE CHARACTERIZATIONS OF WIRELESS POWER TRANSFER USING THE INDUCTIVE COUPLING METHOD - Herawati
Solenoids are a type of inductor that can be made by wrapping an enameled wire in a particular medium. Two solenoids can form a wireless power transfer system as a transmitter solenoid and a receiver solenoid. The purpose of this study is to measure the inductance of the solenoid by several methods and to measure the efficiency of a wireless power transfer system assembled using two solenoids. The measurements of solenoid inductance can be carried out directly and indirectly. Direct measurements were carried out using benchtop and handheld LCR meters, which have frequency settings, while indirect measurements used the LC resonance and series RLC circuits method. In the series RLC circuit method, the source frequency value is validated; thus, the results are close to the actual value. Solenoids whose inductance has been measured will be used as coils in wireless power transfer systems; Circuit efficiency is measured by varying the number of turns, the core material of the receiver solenoid, and the gap between the transmitter and receiver. This research indicates that the measurements of inductance using a benchtop LCR meter, handheld LCR meter, and LC resonance method produce a reasonably accurate value, which is in accordance with the theory that has included the Nagaoka’s constant and is within the tolerance limits for commercial inductors. The efficiency of a wireless power transfer circuit decreases with an increasing gap, increases as the number of turns in the receiver solenoid increases, and increases with increasing the inductance on the receiver solenoid, but efficiency appears to reach saturation value. The efficiency of the circuit will increase significantly if the receiver solenoid is covered with a core material with a high permeability value and low conductivity.